Bromine monoxide mixing ratio profiles in Northern Alaska during spring 2022 via Airborne Multi-AXis Differential Optical Absorption Spectroscopy (AMAX-DOAS) ... - Brockway, Nathaniel; Hajny, Kristian; Shepson, Paul; Simpson, William (NSF Arctic Data Center, 2023)
This data contains 245 bromine monoxide (BrO) profiles measured over the North Slope of Alaska during Spring 2022 during the Clouds, Halogens and Aerosols (CHACHA) field campaign. Scattered-sunlight spectra were recorded via a near-limb airborne spectrometer to retrieve BrO differential slant column densities (dSCDs). Coupled with vertical profiling of the atmosphere by the aircraft, these dSCDs were combined with radiative transfer model results to calculate BrO profiles via optimal estimation. The resulting BrO profiles were grouped into four common patterns using an untrained K-means clustering algorithm. The cluster labels can also be found in this dataset, along with support variables that may be beneficial for chemical modelling (e.g. temperature, ozone concentration, etc.). More details on the methods used and the contents of this dataset can be found in Brockway et al., 2023 (Atmospheric Chemistry and Physics). Any questions about this data can be directed to William Simpson at University of Alaska ...